EFFECTS OF MINERAL FERTILIZATION AND SPRAYING WITH SALICYLIC ACID AND AMINO ACIDS ON THE GROWTH AND PRODUCTIVITY OF INDUSTRIAL POTATOES - K. G. Saaseea; N. J. K. Al-a’amry (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This experiment was carried out at a private field in the eastern Radwaniyah Baghdad for the fall season 2020/2021 and spring 2021 to study the effects of adding mineral fertilizers, spraying salicylic acid and amino acids on some growth traits and yield of industrial potato plants. 200 kg N h-1 , 100 kg P2O5 h-1, 100 kg K2O h-1 and F2 consist of 275 kg N h-1, 180 kg P2O5 h-1, 200 K2O h-1 and F3 consist of 350 kg N h-1, 360 kg P2O5 h-1, 300 K2O h-1 and salicylic acid in three concentrations of 0,50 and 100 mg L-1 ( S1, S2, S3) and amino acids in three concentrations of 0, 1.25 and 2.5 ml L-1 ( A1, A2 , A3) It was carried out as a factorial split plot experiment, where the fertilizer levels (F1, F2 and F3) are in the main plot and the interaction between salicylic acid and amino acids is in the sub plot with three replications. The results showed the superiority of the F3 level by giving the highest plant height in the spring season and the largest number of leaves and leaves area for the two seasons, while the F2 level gave the highest tuber weight and the highest percentage of dry matter for fall seasons, and the concentration S3 and A2 was differed in most of the growth indicators and the yield for both seasons of the experiment.